2020
DOI: 10.3390/nu12010193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ten Weeks of Creatine Monohydrate Plus HMB Supplementation on Athletic Performance Tests in Elite Male Endurance Athletes

Abstract: Creatine monohydrate (CrM) and β-hydroxy β-methylbutyrate (HMB) are common ergogenic aids in the field of sports and are frequently used in an isolated way. However, there are a few studies that have investigated the effect of combining both supplements on different variables related to performance, with controversial results. Therefore, the main purpose of this study was to determine the efficacy and the degree of potentiation of 10 weeks of CrM plus HMB supplementation on sports performance, which was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 64 publications
(82 reference statements)
1
35
0
Order By: Relevance
“…Moreover, the results presented on testosterone and T/C could mean better training adaptation/recovery mediated by the combination of CrM and HMB. This result might have facilitated a better aerobic power in CrM-HMBG during an incremental test (related to individual lactate threshold) [68]. These results were corroborated by a synergistic effect of combined supplementation (CrM plus HMB) on testosterone and T/C and an antagonistic effect on cortisol.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, the results presented on testosterone and T/C could mean better training adaptation/recovery mediated by the combination of CrM and HMB. This result might have facilitated a better aerobic power in CrM-HMBG during an incremental test (related to individual lactate threshold) [68]. These results were corroborated by a synergistic effect of combined supplementation (CrM plus HMB) on testosterone and T/C and an antagonistic effect on cortisol.…”
Section: Discussionmentioning
confidence: 63%
“…Also, they suggested tentative mechanisms, such as mitochondrial biogenesis due to AMP-activated protein kinase (AMPK), Sirt 1 activation, and improved efficiency of carbohydrate, glycogen, and fat metabolisms, to explain the observed changes. A recent study [ 41 ] reported that supplementing rowing athletes with a combination of HMB (3 g/day) and creatine (0.04 g/day) for 10 weeks did not change muscle mass but significantly improved aerobic power. The authors suspected that the improvement in aerobic power was a result of a synergy effect between HMB that caused fiber transformation (driving fast-to-slow fiber switch) together with increased gene expression of gamma co-activator 1-alpha (PGC-1α) and creatine that increased energy availability during exercise via elevated phosphocreatine level in muscle [ 41 ].…”
Section: Nutrition For Rowing Performance In Competition or Trainimentioning
confidence: 99%
“…A recent study [ 41 ] reported that supplementing rowing athletes with a combination of HMB (3 g/day) and creatine (0.04 g/day) for 10 weeks did not change muscle mass but significantly improved aerobic power. The authors suspected that the improvement in aerobic power was a result of a synergy effect between HMB that caused fiber transformation (driving fast-to-slow fiber switch) together with increased gene expression of gamma co-activator 1-alpha (PGC-1α) and creatine that increased energy availability during exercise via elevated phosphocreatine level in muscle [ 41 ]. This means that rowing athletes can save glycogen and gain energy via oxidative capacity when they need endurance.…”
Section: Nutrition For Rowing Performance In Competition or Trainimentioning
confidence: 99%
“…Nutritional supplements were studied in four studies (33.2%) in this Special Issue [1,2,4,12]. Bazzucchi et al [1] and Martin-Rincon et al [4] have studied the effect of polyphenols on muscle recovery, EIMD, and muscle pain, with quercetin (Q) in monotherapy and quercetin plus Zynamite ® (mango leaf extract), respectively.…”
mentioning
confidence: 99%
“…The proteins and amino acids represent the most consumed ergogenic aids. In this Special Issue, two manuscripts [2,12] described the effect of two amino acid supplementation strategies on sports performance. Fernandez-Landa et al [2] created one of a small number of research studies of the additional effect level of amino acid mixing (creatine monohydrate (CrM) and β-hydroxy β-methylbutyrate (HMB)); also, they have identified whether their effects are synergistic in professional rowers.…”
mentioning
confidence: 99%